The Captive Mind In Development Studies. [Pt2] - Alatas, Syed Hussein (1974)
What is a captive mind? Confining ourselves to the Asian context for convenience, a captive mind possesses the following characteristics: A captive mind is the product of higher institutions of learning, either at home or abroad, whose way of thinking is dominated by western thought in an imitative and uncritical manner.